PENGARUH PERTUMBUHAN PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN TERBUKA DI WILAYAH SUMATERA - Cut Fera Rahmanita; Umaruddin Usman (JURNAL EKONOMIKA INDONESIA, 2023)
This study examined the effect of Population Growth and Economic Growth on Open Unemployment in the Sumatra region. This study used quantitative data with a panel data approach, consisting of time series data for six years from 2014 to 2019 and cross-section data from 10 Provinces in the Sumatra region. The analyticals method used was Panel Data Regressions with the Fixed Effect Model. The result partially showed Population Growth positively and significantly influenced Open Unemployment. Meanwhile, Economic Growth negatively and significantly influenced Open Unemployment. The results of the coefficients of determinations revealed that the ability of Population Growth and Economic Growth in explaining Open Unemployment was 82.01%, while the remaining 17.99% is influenced by other variables outside this study